2021
DOI: 10.1108/ijhma-02-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of housing inflation in Turkey: a conditional frequency domain causality

Abstract: Purpose This study aims to investigate whether changes in consumer interest rate, exchange rate and housing supply have permanent effects on housing inflation in Turkey. Design/methodology/approach For this purpose, data from 2010M01 to 2020M06 and changes in consumer interest rate, exchange rate, housing supply and housing inflation were used. Relationships between variables are analyzed first by the Granger causality tests and then the conditional frequency domain causality tests. The conditional frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…When the results obtained are compared with the literature, Akcay et al (2021), Kırca and Canbay (2022), Atasoy and Tanrıvermis (2021), Colak (2021), Yıldırım et al (2021), Gebes o glu (2019), Nneji et al (2013), Goodhart andHofmann (2008), McQuinn andO'Reilly (2008) and Zhu (2006) have obtained similar results in terms of determining the short-and long-term relationships of housing prices with macrovariables. Çetin (2021) determined the relationship between housing prices, inflation and industrial production index as negative and the relationship between interest rates as positive.…”
Section: Conclusion and Discussionsupporting
confidence: 58%
“…When the results obtained are compared with the literature, Akcay et al (2021), Kırca and Canbay (2022), Atasoy and Tanrıvermis (2021), Colak (2021), Yıldırım et al (2021), Gebes o glu (2019), Nneji et al (2013), Goodhart andHofmann (2008), McQuinn andO'Reilly (2008) and Zhu (2006) have obtained similar results in terms of determining the short-and long-term relationships of housing prices with macrovariables. Çetin (2021) determined the relationship between housing prices, inflation and industrial production index as negative and the relationship between interest rates as positive.…”
Section: Conclusion and Discussionsupporting
confidence: 58%
“…According to these results, it is seen that increases in the housing price index negatively affect consumer confidence in the long run, and decreases in it also have negative effects on consumer confidence. It has been concluded that the short-term coefficients between the housing price index and the consumer confidence index are positive and significant Kırca and Canbay (2021) Because NARDL analysis requires the variables used in the analysis to be stationary at level or first differences, unit root analysis is required. Therefore, Lee and Strazizich (2003) unit root test allowing two structural breaks was used to determine the stationarity level of the variables used.…”
Section: Nardl Modelmentioning
confidence: 99%
“…According to the conditional frequency domain causality test results, there is causality for the permanent and mid-term from changes in the consumer interest rate to housing inflation and causality for the mid-term and temporary from changes in the exchange rate to housing inflation. Additionally, it was found that there are causality relationships between changes in the consumer interest rate and changes in the exchange rate [28].…”
Section: Tx Inf Hab Inflation Rate With Housingmentioning
confidence: 99%